Методика фізичної терапії викладачів спеціальної фізичної підготовки закладів вищої освіти зі специфічними умовами навчання після лікування коронавірусної хвороби - Горпинич, Г. Ф.; Horpynych, H. F.; ORCID: https://orcid.org/0000-0001-7982-0981; Шемчук, В. А.; Shemchuk, V. A.; Коник, Г. О.; Konyk, H. O.; Суровов, О. А.; Surovov, O. A.; Аксьонов, Д. В.; Aksonov, D. V. (Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2021. - № 75, т. 1. - С. 104-109, 2021)
Розглянуто проблему пошуку нових форм, методів і засобів фізичної реабілітації після лікування коронавірусної хвороби. Розроблено та апробовано методику фізичної терапії викладачів фізичної та спеціальної фізичної підготовки закладів вищої освіти зі специфічними умовами навчання Національної поліції України, вищих військових навчальних закладів Національної гвардії України після лікування коронавірусної хвороби COVID-19 (SARS-CoV-2).

Given the consequences of the global coronavirus pandemic COVID-19 (SARS-CoV-2), which covered all groups of the population, including representatives of the institutions of the Security and Defense Sector of Ukraine (SDSU), today it is important to find new forms and methods and means of physical rehabilitation of law enforcement officers and servicemen of different categories and age groups after treatment of coronavirus disease, which emphasizes the relevance of the chosen area of scientific intelligence and its practical orientation. Taking into account the results of monitoring of scientific-methodical and special literature (Internet sources) we found that the development and implementation of the system of therapeutic physical culture of different groups (police training and training of SDSU servicemen of different ages and categories) effective methods of physical therapy insufficient number of works is required, which requires further research. The main purpose of the study is to develop and test methods of physical therapy for teachers of physical and special physical training of higher education institutions with specific training conditions of the National Police of Ukraine, higher military educational institutions of the National Guard of Ukraine after treatment of coronavirus COVID-19 (SARS-CoV-2). According to the World Health Organization’s statistics on the global pandemic COVID-19 (SARS-CoV-2), we have found that the vast majority of patients with the above disease have pneumonia (pneumonia). Taking into account this fact, as well as background information on the consequences (complications) after the transfer of the above disease, members of the research group (RG) developed a method of physical therapy for teachers of special physical education institutions (HEI) with specific training conditions of the National Police of Ukraine (NPU), as well as the above specialists of higher military educational institutions (HMEI) of the National Guard of Ukraine (NGU) after treatment of coronavirus COVID-19 (SARS-CoV-2). Comparing the indicators before and after using the method of physical therapy developed by members of the research group, it was found that the results obtained at the end of the pedagogical experiment in the studied teachers (physical training and sports of the National Academy of National Guard of Ukraine, tactical and special physical training of Kharkiv National University of Internal Affairs) increased compared to the original data and these differences are mostly significant (Eg, P≤0.05).

Рассмотрена проблема поиска новых форм, методов и средств физической реабилитации после лечения коронавирусной болезни. Разработана и апробирована методика физической терапии преподавателей физической и специальной физической подготовки учреждений высшего образования со специфическими условиями обучения Национальной полиции Украины, высших военных учебных заведений Национальной гвардии Украины после лечения коронавирусной болезни COVID-19 (SARS-CoV-2).
Methods of physical therapy for teachers of special physical training of higher education institutions with specific learning conditions after treatment of coronavirus disease
Горпинич, Г. Ф. Методика фізичної терапії викладачів спеціальної фізичної підготовки закладів вищої освіти зі специфічними умовами навчання після лікування коронавірусної хвороби / Горпинич Г. Ф., Шемчук В. А., Коник Г. О. та ін. // Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2021. - № 75, т. 1. - С. 104-109. - DOI: https://doi.org/10.32840/1992-5786.2021.75-1.20.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; вищі навчальні заклади зі специфічними умовами навчання; higher educational institutions with specific study conditions; высшие учебные заведения со специфическими условиями обучения; викладачі; teachers; преподаватели; відновлення; recovery; восстановление; компетентності; competence; компетентности; коронавірусна хвороба; coronavirus disease; коронавирусная болезнь; лікувальна фізична культура; therapeutic physical culture; лечебная физическая культура; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; спеціальна фізична підготовка; special physical training; специальная физическая подготовка; фізична терапія; physical therapy; физическая терапия